Two country overlapping-generations model on the global transmission of fiscal policies - Jung, Young Cheol (University of Ottawa (Canada), 2008)
This thesis aims to answer several issues on the global transmission effects of the government fiscal policy. In order to address the issues, this thesis builds a two-country overlapping-generations (OLG) model in which there exist different time preferences, different fiscal policies, and different tax schemes between countries. In particular, the model adopt a utility function with a constant inter-temporal elasticity of substitution (LIES), in which saving positively depends on both labor income and the interest rate. In chapter 1, we try to answer the question; How does the difference in time preferences of individuals affect economic variables in an open economy? and have shown that; first, when two economies with different time preferences are integrated, the capital labor ratio along the transition path is higher or lower than its steady-state value; second, depending on whether the former or the latter happens, the behavior of the balance of payments and the welfare of two countries also differ; third, the less patient country reveals a surplus of current account in spite of an aging population; lastly, economic integration, even if it worsens the current welfare of the less patient country, ultimately improves the future welfare of the country. In chapter 2, we try to answer the question; How is the government debt or budget deficit of a country transmitted to other countries? We have first shown that the crowding out effect of the budget deficit is more pronounced in autarky than in open economy. Second, with an aging population, the current account of the debtor country shows a surplus during the transition path and converges to zero in the steady state. With an increasing population, the current account shows an ambiguous sign during the transition path and reveals a deficit in the steady state; lastly, the government debt lowers the welfare of future generations in both countries. In particular, the welfare of the debtor country continuously declines. In chapter 3, we try to answer the question; Which tax scheme is the best? We have first shown that with respect to capital formation, the consumption tax dominates the capital income tax and the capital income tax dominates the wage tax. Second, the shift to the consumption tax or the capital income tax renders the tax-reformed country a creditor and the other country a debtor. Third, with respect to welfare, the consumption tax is superior to the wage tax but seems not show an advantage over the capital income tax in the tax-reformed country. However, welfare in the other country is somewhat higher under the consumption tax scheme than under other tax schemes of the tax-reformed country; fourth, the tax rate is highest under the capital income tax and is lowest under the consumption tax. Lastly, the transitional analysis shows that the capital income tax can be more rewarding than the consumption tax in the aspect of welfare because the reform to the capital income tax enters its new steady state with a faster speed. Key words: OLG Model, Time Preference, Capital labor ratio, Budget deficit, Government debt, Tax reform, Wage tax, Capital income tax, Consumption tax, Current Account, Net foreign asset, Welfare. JEL Classification: C68, C88, F15, F21, F32,F34, F41, H21, H63
Keywords: Economics, General.